2005
DOI: 10.3758/bf03193082
|View full text |Cite
|
Sign up to set email alerts
|

Both sides get the point: Hemispheric sensitivities to sentential constraint

Abstract: Behavioral studies have consistently reported striking differences in the impact of sentence-level information on the processing of words presented in the right (RVF) versus the left (LVF) visual field, with context effects apparent only for RVF items. The consistent lack of such effects in the LVF has been taken to mean that right hemisphere language comprehension is largely insensitive to messagelevel meaning. We used the functional specificity afforded by event-related potential measures to assess this clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
122
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 55 publications
(71 reference statements)
10
122
2
Order By: Relevance
“…Furthermore, both hemispheres showed similar, task-dependent patterns of priming from lexical and semantic levels of representation (task effect). These findings suggest that cerebral asymmetries observed in other tasks must arise from alternative factors, such as the timecourse of activation (e.g., Koivisto 1997), the representation of different types of semantic relations (e.g., Richards and Chiarello 1995), the predictive use of context information (e.g., Federmeier and Kutas 1999;Federmeier, Mai et al 2005), or the efficacy of strategic, controlled semantic processing (e.g., Burgess and Simpson 1988). Follow-up studies that track asymmetries over time and across processing stages, for example using event related brain potential (ERP) methods, may help to adjudicate between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, both hemispheres showed similar, task-dependent patterns of priming from lexical and semantic levels of representation (task effect). These findings suggest that cerebral asymmetries observed in other tasks must arise from alternative factors, such as the timecourse of activation (e.g., Koivisto 1997), the representation of different types of semantic relations (e.g., Richards and Chiarello 1995), the predictive use of context information (e.g., Federmeier and Kutas 1999;Federmeier, Mai et al 2005), or the efficacy of strategic, controlled semantic processing (e.g., Burgess and Simpson 1988). Follow-up studies that track asymmetries over time and across processing stages, for example using event related brain potential (ERP) methods, may help to adjudicate between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, such differences could arise either because the two hemispheres actually represent these kinds of relationships differently (e.g., Deacon, GroseFifer, Yang, Stanick, Hewitt and Dynowska 2004) or because of more general asymmetries in how each hemisphere processes verbal information. For example, Federmeier and her colleagues (Federmeier and Kutas 1999;Federmeier, Mai et al 2005) have argued that the LH tends to use verbal information predictively whereas the RH integrates old information with new information in a more post-hoc fashion. Lexical association is typically defined by the tendency for one word to lead to the prediction/generation of another, whereas nonassociated, categorically related information will generally be much less predictable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although word processing in both hemispheres seems to be influenced by the message-level meaning information available from a sentence context (e.g., Coulson et al, 2005;Faust, Bar-Lev, and Chiarello, 2003), context seems to affect processing in different ways in each (Federmeier andKutas, 1999, 2002;Federmeier, Mai, and Kutas, 2005;Wlotko and Federmeier, in press). In particular, the LH seems more likely to use the top-down information available from a sentence context to predict features of likely upcoming words, whereas processing in the RH seems to be more stimulus-driven and integrative in nature (see Federmeier, in press, for a more extensive discussion).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Federmeier, Mai, and Kutas (2005) showed that for stimuli presented to either VF, there were nearly identical sentential constraint effects on the N400, a well-studied eventrelated potential (ERP) component that shows specific sensitivities to lexico-semantic manipulations (for a review, see Kutas & Federmeier, 2000). The N400 is thought to be generated bilaterally (perhaps with a greater left than right contribution) in a large portion of the temporal lobe (Van Petten & Luka, 2006), probably including perisylvian regions that correspond to Wernicke's area (and its homologue) as well as areas of the anterior medial temporal lobe associated with semantic memory.…”
mentioning
confidence: 99%